2005
DOI: 10.1007/s10750-004-5712-3
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of aquatic invertebrates of the wheatbelt region of Western Australia in relation to salinity

Abstract: The wheatbelt region of Western Australia has been extensively cleared of indigenous vegetation for agriculture and is now severely affected by dryland salinity. Wetlands that were once freshwater are now saline and others are under threat, as are the animals and plants that inhabit them. Rising groundwater is also affecting the many naturally saline playas. To provide a framework for setting conservation priorities in this region a biological survey was undertaken, including sampling of aquatic invertebrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
152
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(173 citation statements)
references
References 88 publications
16
152
3
2
Order By: Relevance
“…Anthropogenic (secondary) salinisation of arid and Mediterranean lands occurs globally and influences the distribution of aquatic assemblages across the landscape (Roberts & Irving-Bell, 1997;Halse et al, 2003;Hart & Lovvorn, 2005;Pinder et al, 2005;Piscart et al, 2005b). General consensus exists that increasing river and wetland salinity has potential to cause local extinctions, alterations in ecosystem function and extensive environmental damage (Halse et al, 2003;Kefford et al, 2003;Jardine et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Anthropogenic (secondary) salinisation of arid and Mediterranean lands occurs globally and influences the distribution of aquatic assemblages across the landscape (Roberts & Irving-Bell, 1997;Halse et al, 2003;Hart & Lovvorn, 2005;Pinder et al, 2005;Piscart et al, 2005b). General consensus exists that increasing river and wetland salinity has potential to cause local extinctions, alterations in ecosystem function and extensive environmental damage (Halse et al, 2003;Kefford et al, 2003;Jardine et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…General consensus exists that increasing river and wetland salinity has potential to cause local extinctions, alterations in ecosystem function and extensive environmental damage (Halse et al, 2003;Kefford et al, 2003;Jardine et al, 2007). Halse et al (2003) predicted that approximately one-third of aquatic invertebrate diversity in the inland southwest of Western Australia (WA) will disappear with the expansion of secondary salinisation, and Pinder et al (2005) suggested that up to 100 species that are largely restricted to the inland southwest are at risk of extinction. However, biotic factors, such as behaviour, are also important drivers of organism distribution, but considered less frequently (Stoks & McPeek, 2003;Blaustein et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations